2017
DOI: 10.1016/j.celrep.2017.11.094
|View full text |Cite|
|
Sign up to set email alerts
|

A Global Interactome Map of the Dengue Virus NS1 Identifies Virus Restriction and Dependency Host Factors

Abstract: Dengue virus (DENV) infections cause the most prevalent mosquito-borne viral disease worldwide, for which no therapies are available. DENV encodes seven non-structural (NS) proteins that co-assemble and recruit poorly characterized host factors to form the DENV replication complex essential for viral infection. Here, we provide a global proteomic analysis of the human host factors that interact with the DENV NS1 protein. Combined with a functional RNAi screen, this study reveals a comprehensive network of host… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
119
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(126 citation statements)
references
References 71 publications
7
119
0
Order By: Relevance
“…Overlaying interactions from the benchmark dataset and previously published replication phenotypes as well as 149 well-characterized human-human PPIs on the DENV-human PPI network highlighted specific interactions of interest. This included the previously identified interactions between NS1 and complement component C4A (Avirutnan et al, 2010), EI24 and the TRiC chaperone complex (Hafirassou et al, 2017), NS2B3 interacting with members of the CTLH complex (Kobayashi et al, 2007), and NS5 with the PAF1 complex PAF1C (Krogan et al, 2002). Interactions between DENV proteins and p62 (SQSTM1), TTC37, and TRIM26 were also detected, all of which were previously implicated in DENV replication (Marceau et al, 2016; Metz et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overlaying interactions from the benchmark dataset and previously published replication phenotypes as well as 149 well-characterized human-human PPIs on the DENV-human PPI network highlighted specific interactions of interest. This included the previously identified interactions between NS1 and complement component C4A (Avirutnan et al, 2010), EI24 and the TRiC chaperone complex (Hafirassou et al, 2017), NS2B3 interacting with members of the CTLH complex (Kobayashi et al, 2007), and NS5 with the PAF1 complex PAF1C (Krogan et al, 2002). Interactions between DENV proteins and p62 (SQSTM1), TTC37, and TRIM26 were also detected, all of which were previously implicated in DENV replication (Marceau et al, 2016; Metz et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Several systematic and unbiased approaches to identify host factors involved in flavivirus replication have been conducted to date (Hafirassou et al, 2017; Mairiang et al, 2013; Marceau et al, 2016), but none have systematically identified flavivirus-host PPIs for multiple flaviviruses directly in the host cells in which they replicate, human and mosquito.…”
Section: Introductionmentioning
confidence: 99%
“…For vertebrate‐ and insect‐infecting viruses, RACK1 is known to be targeted during replication. For example, dengue virus NS1 protein interacts with RACK1 to facilitate virus replication without affecting viral translation (Hafirassou et al ., ), although the underlying mechanism of RACK1 in dengue virus replication remains unknown. The interaction of infectious bursal disease virus protein VP5 with RACK1 inhibits apoptosis and thereby keeps cells suitable for virus replication (Lin et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…RPS25 was the fourth top hit in a genome-wide haploid genetic screen for dengue virus (DENV) host factors and was also identified in a screen of the closely-related Zika virus (ZIKV) (Marceau et al, 2016;Ooi et al, 2019). siRNA studies in other cell lines have further implicated both RPS25 and RACK1 as host factors for DENV propagation (Hafirassou et al, 2017), and RPS25 but not RACK1 was shown to be important for the propagation of the yellow fever virus (YFV), another flavivirus (Petrova et al, 2019). Flaviviruses are positive-sense RNA viruses, and DENV and ZIKV have capped genomic RNAs (gRNAs) implying that their translation could share a common mechanism with canonical cellular capped mRNAs.…”
Section: Rps25 Loss Is Protective Against Flavivirus Infection and Thmentioning
confidence: 99%
“…Flaviviruses are positive-sense RNA viruses, and DENV and ZIKV have capped genomic RNAs (gRNAs) implying that their translation could share a common mechanism with canonical cellular capped mRNAs. Given the prior connection of RPS25 to IRES-mediated translation events, one interpretation from the potent DENV resistance phenotype of RPS25-deficient cells is that DENV utilizes a specialized translation mechanism despite the presence of a cap on its gRNA (Hafirassou et al, 2017). Such an interpretation may be supported by the observation that DENV translation can operate under cellular conditions where cap-dependent translation is inhibited (Edgil et al, 2006), and the recent suggestion that the DENV and ZIKV 5' untranslated regions harbor certain IRES properties (Song et al, 2019).…”
Section: Rps25 Loss Is Protective Against Flavivirus Infection and Thmentioning
confidence: 99%